Anxiety and depression among university nursing students: application of prevention programs - Παναγιωτοπούλου Αγγελική; Α. Πασχάλη Αντωνία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
This literature review aims to investigate Cognitive Behavioral Programs (CBT) that are applied worldwide and their effectiveness on the prevention of anxiety and depression in nursing students. In the first part of the review, the importance of studying these programs and their application in the nursing population are mentioned. Contemporary research data on the prevalence of anxiety and depression in nursing students are examined and comparisons are made with studies looking upon general student population of the same age. Factors that trigger or protect against the onset of these problems are presented. CBT programs are discussed, in relation to anxiety disorders and depression in relevance to the nursing population, while in the later section contemporary research findings of CBT programs that have been applied to nursing students are presented. The results of these programs show that there is a significant decrease of the anxiety and improvement of the students’ mood, which points to the importance of primary prevention in the academic environment in order to ensure students’ mental health and quality of life.